Modelo de susceptibilidad por movimientos en masa en Lima Metropolitana y el Callao - Villacorta Chambi, Sandra Paula (2014)
[ENG] The results of the geological and geodynamic assessment are presented. Besides analysis of landslide susceptibility is made which are of high potential risks to Metropolitan Lima and Callao. This involves the characterization and inventory of surface geodynamic processes, performed by the Geological Institute of Peru (INGEMMET) between 1970 and 2011, which have lead us to identify the critical areas vulnerable to these surface geodynamic processes. In the study area, there have been a total of 848 recent and ancient geological hazards. To do this, we haveused technical literature sources, tools of remote sensing (aerial photographs and satellite images). A fieldwork was done as well, for mapping and geo-referencing processes and represent them in thematic maps using Geographic Information Systems (GIS). To prevent potential landslide disasters in Lima and Callao Metropolitan is necessary to evaluate in detail the critical areas of high susceptibility. In this regard, the susceptibility map is a key tool in the decision making process and significantly contributes to the management of geological risk regions involved.